Fantasy and Contemporary Cities: Urban Spaces in YA Booktube Reviews - Sánchez-Rebato Valiente, Clara (Street Art & Urban Creativity, 2025)
This article investigates the role of cities in Young Adult book reviews on Booktube, focusing on content created by female booktubers from Spain, the United Kingdom, and the United States. It reviews the community of Booktube, as well as its connection to participatory culture and literary theory related to fantasy and contemporary genres, which are essential for this study. A multimodal discourse analysis, supported by social semiotics, is employed as the methodology. The findings reveal that booktubers emphasize world-building, distinguishing between realistic and fantastical settings. Fantasy reviews often draw on the booktuber’s subjectivity through personal experiences in similar cities or intertextual and cultural references. In contrast, contemporary book reviews utilize urban settings to reflect on current issues. Overall, the research highlights the relationship between subjectivity and city representation in online book reviews, employing personal memories and cultural references to create engaging and informative content.